Konsep Pembelajaran Pluralisme pada Anak Usia Dini dalam Buku Aku Anak Indonesia - Subur, Dwi Rohman Soleh, Musyafa Ali (Universitas Veteran Bangun Nusantara, 2022)
Indonesia is a pluralistic country, consisting of a diversity of tribes, races, cultures and religions. Indonesia's diversity must be introduced, taught and instilled early so that children have a sense of love for the homeland and appreciate all differences. The purpose of this study is to describe and analyze the concept of pluralism learning in early childhood in the book I am Children's Indonesa by Theresia Praditya. This research is a Research Library where researchers review books as research material. The data source was obtained from the book Aku Anak Indonesia, a data collection technique using documentation. Data analysis is carried out in three stages (1) of data reduction (2) presentation (3) verification and conclusion. The results of this study show that the concept of pluralism learning in the book aku anak Indonesia by Theresia Praditya is taught through, uniformity of clothing, diversity of RAS, diversity of worship, cultural diversity, and other concepts of introduction, namely through social attitudes.